PERFORMANCE OF MINIATURE PUNGANUR CATTLE OF ANDHRA PRADESH, INDIA - B. Ekambaram; M. Kalyana Chakravarthi; G. Alexander (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Punganur breed of cattle in Andhra Pradesh is under the threat of extinction and efforts are being made for conservation, propagation of this breed under in situ conservation. All breedable female animals were bred to Punganur bulls available by natural service. The average birth weights of male and female calves were 10.31 ± 0.43 kg and 10.35 ± 0.75 kg, respectively. The mean height at withers, chest girth ,body length, pin bones width, paunch girth, poll length, tail length, and ear length in male calves were 45.81 ± 1.05, 46.72 ± 1.34, 43.90 ± 1.29, 7.54 ± 0.73, 45 ± 1.2, 18.09 ± 0.94, 27.45 ± 1.77, 8.54 ± 0.7 cm, respectively. Majority of the calves were born with a mixture of white and brown coat colour, black muzzle, black colour hooves and black switch. The average lactation milk yield was 457.5 ± 81 liters with a lactation length of 153 ± 24 days. The average daily milk yield and peak yield were 3.04 ± 0.16 and 3.90 ± 0.17 liters respectively with an average 5.4 % fat and 9.53 % S.N.F.